Creation of a Pluralistic Security Community and its relevance in the case of India-Pakistan - Mukand, Rahul (International Journal of Advanced Research in Peace, Harmony and Education; Vol 10 No 1 (2025): International Journal of Advance Research in Peace, Harmony and Education, 2025)
This paper examines the pluralistic security community that is articulated by Arie M. Kacowicz and connects it to Karl W. Deutsch’s foundational ideas on security communities. It seeks to identify common grounds for establishing such a community between India and Pakistan. Using secondary sources as its methodological foundation, the paper provides an analysis of the challenges—termed “stumbling blocks”—that hinder the formation of a pluralistic security community. These obstacles are briefly discussed before drawing conclusions. Kacowicz identifies three “zones of peace,” which form the basis for understanding the evolution of peaceful coexistence among states. Zone, I encompass states that are inherently status quoist but face potential threats of civil war, domestic crises, or international conflicts. Zone II includes states that have achieved stable peace, characterised by minimal conflict and a predominantly status quoist outlook. Zone III, the most advanced, consists of states that have established the “pluralistic security community.” These states uphold shared democratic institutions, cultivate interdependence, and place a strong emphasis on peace. While tensions may exist in this zone, they do not escalate into violent intra- or inter-state conflicts. Focusing on India and Pakistan—two nations marked by complex ethnic compositions, deep-seated religious and cultural differences, contrasting political systems, and a fraught history—the paper explores the conditions necessary for transitioning from negative peace (devoid of conflict) to positive peace (sustainable and constructive relations). The paper outlines the pathways and prerequisites for leveraging Punjabiyat to foster a pluralistic security community between these historically adversarial neighbours.